ROZWÓJ REGIONALNY POLSKI W PERSPEKTYWIE CZŁONKOSTWA W UNII GOSPODARCZO-WALUTOWEJ - Gruchman, Bohdan (Wydział Prawa i Administracji UAM, 2006)
Poland’s membership in the European Monetary Union is still a relatively distant event. However if one considers the slow pace of structural change in regional development the exciting differences in this field in Poland could amount to a major obstacle in the smooth transition to the single currency even if this takes more years to come. The transition period to the market economy (1989/90-2004) did not eliminate existing sharp differences in the development level of the Polish regions. They still exist despite the investment outlays considerably augmented owning to EU pre-accession aid and the Integrated Operational Programme of Regional Development for the years 2004-2006. In order to obtain satisfactory results from structural Funds forseen for the period 2007-2013 it is necessary to better coordinate investment projects stemming from different sectoral programmes with the 16 regional ones (in order to get higher spill-over effects or value added). More attention should be paid to investment in human capital. Simultaneously the territorial and social mobility of labour in Poland should be increased and greater wage elasticity introduced in order to better prepare the economy for a unified monetary policy and possible external shocks. Hence, the current concept of regional development policy should be revised substantially.
DEVELOPMENT OF THE REGIONAL STRUCTURE FOR POLAND’S MEMBERSHIP IN THE MONETARY UNION